MAKNA FILOSOFIS NILAI-NILAI SILA KE-EMPAT PANCASILA DALAM SISTEM DEMOKRASI DI INDONESIA - Yusdiyanto Yusdiyanto (Fiat Justisia: Jurnal Ilmu Hukum, 2016)
Indonesia is a nation that has a philosophy of Pancasila, therefore, any values in the principles of Pancasila should be applied in the life of the nation. As principles number 4th Pancasila mention "Populist-led by the inner wisdom consultative / representative". Means, which put forward the principle of deliberation and consensus through its representatives and representative agencies in fighting the people's mandate. This view provides the justification that democracy in this republic run through election mechanism. The democracy that sovereignty of the people in its implementation need to be inspired and be integrated in the precepts that other, accompanied by a sense of responsibility to God Almighty, upholding human values in accordance dignity and human dignity, ensure and strengthen the unity of the nation and utilized for the realization of social justice , Their spirit of Pancasila democracy that led to citizens looking at each other, respect, accept and cooperation in the form of unity of mutual interest between the "public" or "state". Keywords: Democracy, Election Mechanism, Pancasila